FUNCTIONAL STATUS OF VASCULAR ENDOTHELIUM IN DIABETES MELLITUS - Saboor, Muhammad; uddin, Moin; Ajmal, Muhammad; Ilyas, Samina (Journal of Ayub Medical College Abbottabad, 2014)
Normal endothelial cells synthesize and release biologically active substances. These substances maintain homeostasis through adequate blood flow, delivery of nutrients, activation and inhibition of coagulation proteins, prevention of thrombosis and diapedesis of leukocyte. Endothelial dysfunction implies failure of vascular endothelium to perform its normal functions of vasodilatation and vasoconstriction. It results from an imbalance between endothelium derived constricting and relaxing factors. Altered endothelial cell activity predisposes to increased production of vasoconstrictors, i.e., prostaglandins, endothelins, glycated proteins, endothelial adhesion molecules and platelet and vascular growth factors. These changes enhance vasomotor tone, vascular permeability, growth and remodeling of the vessels. Diabetes is associated with abnormalities of vascular endothelium. Several regulatory vasodilators and vasoconstrictors are altered in diabetes leading to diabetic vascular complications. Balance between dilating and constricting substances is altered and is shifted towards vasoconstriction in diabetes. Disturbances in the endothelial functions lead to increased platelet adhesion and aggregation in patients with diabetes. Activated platelets interact with endothelial cells and leukocytes in the genesis of atherosclerosis. High level of Von Willebrand factor(vWF) is a consistent finding in diabetes. Increased vWF level is one of the major risk factors for the development of micro vascular complications. High levels of vWF may predict cardiovascular disease progression in diabetes mellitus. Keywords: Vascular, endothelium, diabetes mellitus